2019
DOI: 10.2478/pielxxiw-2019-0030
|View full text |Cite
|
Sign up to set email alerts
|

Life satisfaction of the pregnant women

Abstract: Introduction. Satisfaction with life is a general assessment of satisfaction with one’s own achievements and living conditions on many levels. This includes human cognitive processes, expressing the emotional state that occurs as a result of achieving a specific goal. According to Juczyński, the assessment of life satisfaction is the result of confronting one’s own situation with the adopted criteria. If the result of the comparison is positive, the implication is the feeling of satisfaction. Satisfaction with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
2
1
1
Order By: Relevance
“…al., 2014;Battulga et al, 2021;Turk et al, 2017), our results failed to support these findings. Moreover, level of education was related neither to life satisfaction nor to happiness in our sample, on the contrary to Skurzak et al (2019), who found that pregnant women with higher education were more satisfied in life. While studies on gestational age and level of life satisfaction in pregnancy reported mixed findings in line of decreasing, stable to increasing life satisfaction (Aasheim et al, 2014;Branecka-Wozniak et al, 2020;Dyrdal et al, 2011), gestational age was not a predictor of life satisfaction and happiness in current study.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…al., 2014;Battulga et al, 2021;Turk et al, 2017), our results failed to support these findings. Moreover, level of education was related neither to life satisfaction nor to happiness in our sample, on the contrary to Skurzak et al (2019), who found that pregnant women with higher education were more satisfied in life. While studies on gestational age and level of life satisfaction in pregnancy reported mixed findings in line of decreasing, stable to increasing life satisfaction (Aasheim et al, 2014;Branecka-Wozniak et al, 2020;Dyrdal et al, 2011), gestational age was not a predictor of life satisfaction and happiness in current study.…”
contrasting
confidence: 99%
“…Other studies that examined life satisfaction in pregnant women depending of sociodemographic variables found that maternal age, parity (Aasheim et al, 2014), relationship status and education were related to higher life satisfaction (Skurzak et al, 2019). More specifically, first-time mothers of advanced age reported lower life satisfaction (Aasheim et al, 2014;Battulga et al, 2021), while pregnant women with a spouse and higher education reported higher life satisfaction (Skurzak et al, 2019). Younger women were also happier during pregnancy than older women (Battulga et al, 2021;Turk et al, 2017).…”
Section: Journal Of Happiness and Healthmentioning
confidence: 98%
“…Cronbach’s alpha reliability index for the SWLS is 0.81 (Polish version) [ 31 , 32 ]. The SWLS scale is a frequently used scale to assess life satisfaction in perinatal women [ 33 , 34 , 35 , 36 , 37 ]. Stress was assessed on the basis of the Perceived Stress Scale (PSS-10), using the Polish version adapted by Juczyński and Ogińska-Bulik [ 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Yaşam memnuniyeti, her insan tarafından benzersiz bir şekilde deneyimlenir ve kişilik özelliklerine, bireysel kaynaklara, dış etkenlere, yaşam koşullarına, yaşam olaylarına ve bunların etkileşimine bağlıdır 26 . Yaşam memnuniyeti, genellikle mutluluk ve yaşam kalitesi ile eşanlamlı olarak kullanılmaktadır 27 .…”
unclassified